Winter quarters : the 1846-1848 life writings of Mary Haskin Parker Richards - Richards, Mary Haskin Parker, 1823-1860 (Life writings of frontier women ;, 1996)
Mary Richard's journals and letters record a young woman's rare, but richly detailed view of life in the temporary Mormon pioneer communities in Iowa.